Who's at risk in the backcountry? Effects of individual characteristics on hypothetical terrain choices. (October 2018) - Mannberg, Andrea; Hendrikx, Jordy; Landrø, Markus; Ahrland Stefan, Martin
Abstract: We use data from an online survey in Norway (N = 467, 73% male; age: M = 34, SD = 10.07) to analyze hypothetical choices in hazardous avalanche terrain. We further analyze differences in stated preference for and willingness to accept to ski relatively risky terrain. Our results suggest that risk attitudes and perception constitute important determinants for hypothetical terrain choices. We further find that many participants accept to ski runs that they perceive to be significantly riskier than their most preferred choice. Our results also suggest that while backcountry skill and experience correlate with preferences for steep terrain, these factors hold no explanatory power for accepting to ski a risky run. Finally, we find indications that social admiration plays a role in decisions related to avalanche risk. Our findings highlight the role of risk attitudes and perception, and social factors in backcountry skiing, and gives implications for future research and avalanche education. Highlights: Attitudes and perception of risk predict hypothetical choices in avalanche terrain Social factors may play an important role in decisions related to avalanche risk Riders accept to ski terrain that is riskier than their most preferred run Neither experience nor travel skills predict acceptance to ski risky terrain